EVALUASI SISTEM PINJAMAN ONLINE SYARIAH: APAKAH PINJOL SESUAI PRINSIP-PRINSIP SYARIAH? - Miqdad, Muhammad; Asdar, Syawal Tawakkal; Azzir, Muhammad Fatir Aufa; Al-Faruq, Muhammad Dzaki (Taksasila Edukasi Insani, 2024)
This study aims to evaluate the alignment of operational management in sharia-compliant online lending systems with Islamic principles, focusing on efficiency, fairness, and sustainability. The research employs a qualitative descriptive method with a literature review approach, analyzing relevant academic journals, books, and official reports. The study finds that while many online lending platforms adhere to sharia principles such as using qard al-hasan and murabahah contracts, challenges remain regarding transparency, risk management, and long-term sustainability. The research contributes to the theoretical understanding of how sharia principles can be integrated into operational management in fintech. Practically, the findings suggest that sharia-compliant online lending platforms need to improve transparency and risk management strategies. The limitations of this study are due to the use of secondary data, which limits the ability to generalize findings. Further research using mixed-methods approaches and a focus on technological advancements is recommended. Keywords : sharia-compliant, online lending, operational management, fintech.